Penguatan Budaya Sadar Bencana Bagi Generasi Muda Desa Terdampak Erupsi Gunung Semeru di Desa Sumberwuluh, Kecamatan Candipuro, Kabupaten Lumajang - Ali Badrudin; Banun Kusumawardani; Tecky Indriana; Agustina Dewi Setyari; Indra Nurtjahjaningtyas; Arif Mohammad Siddiq; Nindha Ayu Berlianti; Nilasari Dewi (Journal of Community Development, 2025)
Mount Semeru as one of the highest mountains on the Java island has significant volcanic activity to date. The eruption of this volcano had a considerable impact on the surrounding area, including Sumberwuluh Village, Candipuro District, Lumajang Regency. The impact felt by the community is not only physical damage but also trauma. Therefore, a disaster awareness culture needs to be built and strengthened early in order to reduce the impact caused when a disaster occurs. The Institute for Research and Community Service (LP2M) of the University of Jember in collaboration with the Regional Disaster Management Agency (BPBD) of Lumajang Regency carried out service activities for elementary school students and teachers in Sumberwuluh Village with the aim of strengthening the culture of disaster awareness. This activity has been attended by students and teachers from SDN Sumberwuluh 1, SDN Sumberwuluh 2, SDN Sumberwuluh 3, SDN Sumberwuluh 4, SDN Sumberwuluh 5 and MI Miftahul Ulum. This is carried out through two stages, socialization about the importance of disaster preparedness and direct practice of disaster preparedness consisting of water boat evacuation, webbing and trauma healing. This program has succeeded in increasing disaster preparedness awareness through disaster education from an early age. In addition, this activity also succeeded in improving knowledge and practical skills in disaster preparedness by 88% and building a better mentality and readiness in dealing with emergency situations.